THE WORK OF SIMULTANEOUS TEACHER-STUDENT AND PEER INTERACTION IN ENGLISH LEARNING - Wildona Zumam; Mohammad Amiruddin (IKIP Siliwangi, 2023)
The work of interaction between teacher-student and peer contact in English language acquisition was investigated in this study. This is an ex post facto study that employs a quantitative technique. In this study, students serve as members of the population. The proportionate stratified random sampling approach is used to choose a sample. A multiple regression approach is used to examine the data. The study found that the work of interaction between teacher-student and peer contact in English language acquisition is 0.285 (28.5%). The job of contact between instructor and student, as well as peer interaction, both work on students' English proficiency level. The correct relationship between teachers and students results in a conducive classroom for language acquisition. It is necessary for teachers to provide students with appropriate engagement with their surroundings in order to set up the classroom and serve the students with significant input. Members of the academic society are expected to have access to a proper teaching style in learning.Â Keywords:Â Teacher-Student Interaction; Peer Interaction; Simultaneously; English Learning